How can challenges in left behind places be addressed? Learning from Greater Lille, Nantes, the Ruhr region, San Antonio and Estonia. (Transactions of the Association of European Schools of Planning, 2022)
Addressing issues of regional inequalities and supporting ‘left behind’ regions is a global issue, but analysis of international regions that have successfully levelled up is limited. Developing and implementing effective place-based policies is critical for recovery from the Covid-19 pandemic but remains an under-explored issue. This paper provides insight into different policies and tools used to support left-behind places. Comparing experiences of addressing socio-economic challenges in Greater Lille, Nantes, the Ruhr region, San Antonio and Estonia, it discusses what ingredients for successfully addressing inequalities are, what has worked well, and future challenges. It identifies seven “foundations” for levelling up and stresses the importance of levelling up “within” regions and not just levelling up “of” regions given how despite economic growth in the case study places, clear socio-economic disparities continue to exist. In particular, it debates opportunities to support levelling up through financial management and governance tools.
Keywords: left behind places; levelling up; regional inequalities; socio-economic disparities